2015
DOI: 10.1177/0003122415577989
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Diversity and Social Trust

Abstract: In this paper we argue that residential exposure to ethnic diversity reduces social trust. Previous within-country analyses of the relationship between contextual ethnic diversity and trust have been conducted at higher levels of aggregation, concealing substantial variation in actual exposure to ethnic diversity. In contrast, we analyze how ethnic diversity of the immediate micro-contextwhere interethnic exposure is inevitableaffects trust. We do this using Danish survey data linked with register-based data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(98 citation statements)
references
References 71 publications
(132 reference statements)
3
93
1
1
Order By: Relevance
“…Fear of crime is increased in countries and neighborhoods with higher proportions of immigrants (Ceobanu 2010;Hooghe and de Vroome 2016;Semyonov et al 2012;Visser, Scholte, and Scheepers 2013). Relatedly, research from Denmark has found that social trust is lessened in immigrant-heavy neighborhoods (Dinesen and Sønderskov 2015), and that the post-September 11 era in Denmark has amplified the perceived threat of Danish Muslims, including many immigrants (Mouritsen and Olsen 2013; Rytter and Pedersen 2014). Research on immigration beliefs after violent events has not studied fear of crime, though.…”
Section: Possible Factors Shaping Immigration Beliefs and Major Eventsmentioning
confidence: 99%
“…Fear of crime is increased in countries and neighborhoods with higher proportions of immigrants (Ceobanu 2010;Hooghe and de Vroome 2016;Semyonov et al 2012;Visser, Scholte, and Scheepers 2013). Relatedly, research from Denmark has found that social trust is lessened in immigrant-heavy neighborhoods (Dinesen and Sønderskov 2015), and that the post-September 11 era in Denmark has amplified the perceived threat of Danish Muslims, including many immigrants (Mouritsen and Olsen 2013; Rytter and Pedersen 2014). Research on immigration beliefs after violent events has not studied fear of crime, though.…”
Section: Possible Factors Shaping Immigration Beliefs and Major Eventsmentioning
confidence: 99%
“…Thus, a wealth of academic literature reveals a positive relationship between out-group size and manifestations of prejudice (e.g., Blalock, 1957;Coenders, 2001;Gorodzeisky & Semyonov, 2015;Quillian, 1995Quillian, , 1996Scheepers, Gijsbert, & Coenders, 2002;Semyonov, Raijman, & Gorodzeisky, 2006), whereas other literature finds no such evidence (e.g., Coenders, Lubbers, & Scheepers, 2005;Hjerm, 2007Hjerm, , 2009McLaren, 2003;Semyonov et al, 2004) and even identifies a negative relationship (e.g., Lubbers, Coenders, & Scheepers, 2006). This controversial discussion can be tackled if we take into account aspects such as the scale of the scope of study (Kaufmann & Harris, 2015;Pottie-Sherman & Wilkes, 2017;Rodon & Franco-Guillén, 2014;van Heerden & Ruedin, 2017), the opportunities that the receiving society offers for meaningful interethnic contact (Dinesen & Sønderskov, 2015), and other contextual variables to help interpret the results obtained.…”
Section: Out-group Sizementioning
confidence: 99%
“…While a number of articles have examined the impact of trust on various outcomes that promote growth, relatively few articles explore the mechanisms that form or destroy trust. The factors that form trust can be categorized into two branches, historical, or inherited, factor, and contemporaneous, or experiential, factor (Dinesen & Sønderskov, ). Perhaps due to a more convenient way of identification, more research has explored the effect of historical factors, such as the socialist regime (Lichter et al, ), conflict (Osborne et al, ), and slavery (Nunn & Wantchekon, ), that last even through generations .…”
Section: Literature On Trust and Market Experiencementioning
confidence: 99%